PEMBENTUKAN OPINI PUBLIK MELALUI INSTRAGRAM EYE.ONE.PALESTINE DALAM KONFLIK ISRAEL PALESTINA - Fani Ardia Putri; Siti Fajrina (Universitas Sunan Drajat Lamongan, Indonesia, 2026)
The rapid development of social media has significantly transformed the landscape of globalpolitical communication, particularly in shaping public opinion on international conflicts. Oneaccount actively disseminating humanitarian narratives is the Instagram accountEye.one.Palestine, which consistently publishes content related to the conflict between Israeland Palestine. This study aims to analyze how the digital communication strategies employedby the account contribute to the formation of public opinion among its followers. This researchapplies a qualitative method with a content analysis approach, examining posts, captions,visual elements, and audience engagement patterns such as comments, likes, and shares. Datawere collected through direct observation of published content within a specific period andanalyzed using agenda-setting theory, framing theory, and the spiral of silence theory. Thefindings indicate that Eye.one.Palestine strategically utilizes emotionally compelling visuals,persuasive narratives, and targeted hashtags to cultivate empathy and solidarity towardhumanitarian issues in Palestine. The framing pattern predominantly emphasizes civiliansuffering, injustice, and the urgency of international support. Audience interaction intensitydemonstrates the emergence of a digital discursive space that reinforces collective opinion andencourages participation in the form of symbolic support and social action.This study concludes that Instagram plays a significant role as a medium for constructingsocial reality in global conflicts, where non-state actors can influence public perception acrossnational boundaries. The research contributes to the field of digital political communicationand the dynamics of public opinion formation in the social media er